BIOLOGICAL CHARACTERIZATION OF PHAGES OF XANTHOMONAS CAMPESTRlS PV. MALVACEARVM - J. P. VERMA, S. K. DUTTAMAJUMDER* AND (Indian Phytopathology, 2002)
The biological behaviours of two types of Xcm phages (Grp-l, lysing Lac" Xcm; Grp-Il, lysing Lac’ Xcm isolates) were characterized. Both groups of Xcm phages possessed similar burst size of 77 but differed in latent period and rise period (respectively 22 min and 18-22 min for Grp-I phage, and 28 min and 22 min for Grp-II phage). Adsorption rate constant (K) varied from 4.35 X 10-’1to 5.81 X 10-’1ml/min for both phage groups. Thermal inactivation point (TIP) was 78Â°C for both types of phages. Grouping of Xcm ph;)ge5 on the basis of lactose utilization behaviour of Xcm was not rigid and only 65.5 per cent of Xcm isolates could differentiate phages into two groups. In heterologous phage-bacteria combinations, efficiency of plating (E.O.P.) was greatly reduced indicating the possible operation of host restriction and modification phenomena between the phage groups and Xcm isolates.